Feasibility of an exercise programme in elderly patients undergoing allogeneic stem cell transplantation – a pilot study. (3rd November 2015) - Schuler, M.K.; Hornemann, B.; Pawandenat, C.; Kramer, M.; Hentschel, L.; Beck, H.; Kasten, P.; Singer, S.; Schaich, M.; Ehninger, G.; Platzbecker, U.; Schetelig, J.; et al.
Abstract : It has been demonstrated that physical exercise benefits younger patients undergoing allogeneic haematopoietic stem cell transplantation (allo‐HSCT). We designed a prospective pilot study investigating whether elderly patients (>60 years) would also be able to participate in such a programme. It consisted of physiotherapist‐supervised alternating endurance and resistance workouts on 6 of 7 days a week. Sixteen consecutive patients undergoing allo‐HSCT were enrolled into the study. The median age was 64.5 years. Twelve patients participated in the programme until the time of discharge (75%) from the transplant unit. Therefore, the predefined criteria regarding feasibility were met. The reason for drop out was transplantation associated mortality in all patients ( n  = 4). Adherence was very good with a median of 85% attended training sessions. No adverse events were recorded. The endurance capacity dropped by 7% and lower extremity strength improved by 2% over time. Quality of life decreased during the study period, with global health being significantly worse at the time of discharge. In conclusion, a combined and intensified strength and endurance exercise programme is feasible and safe in a population of elderly patients undergoing allo‐HSCT. Further research should focus on exploring effect sizes of such an intervention by conducting randomised controlled trials.